Benzene toxicity in front attendants of fuel dealer stations - Feitosa, Paola de Araújo (2021)
Hydrocarbon is a substance used in various occupational processes, such as in petrochemical industries, rubber mills, steel mills and fuel supply locations, scientifically known as Benzene. The most exposed population refers to workers who work directly with the product, who as a result of exposure suffer side effects that are extremely harmful to health. To identify chronic and acute changes in poisoning and changes at the DNA level caused by Benzene. This is a literature review, based on articles published in the last two decades, found in the Google Academic, Scielo and Lilacs databases, selected according to their relevance to the outlined objectives. 11 support materials were discussed to support the research, which confirm that over exposure, workers may develop leukemia and showed that white cells tend to be the most affected in the long term. It is important to periodically assess the health of workers and analyze possible pharmacological treatments to maintain the health of the employee, avoiding intoxication, or if it is not possible to avoid it, start your treatment as quickly as possible.